2014
DOI: 10.1016/j.actpsy.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Norms of age of acquisition and concreteness for 30,000 Dutch words

Abstract: a b s t r a c t a r t i c l e i n f oWord processing studies increasingly make use of regression analyses based on large numbers of stimuli (the socalled megastudy approach) rather than experimental designs based on small factorial designs. This requires the availability of word features for many words. Following similar studies in English, we present and validate ratings of age of acquisition and concreteness for 30,000 Dutch words. These include nearly all lemmas language researchers are likely to be interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
159
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(171 citation statements)
references
References 44 publications
2
159
0
10
Order By: Relevance
“…Primjerice, baza konkretnosti koju su izradili Brysbaert, Warriner i Kuperman (2014b) sadr`ava 40.000 engleskih leksema, me|utim bez podatka o vrsti rije~i kojoj pripadaju. Sli~na baza izra|ena je i za nizozemski (Brysbaert et al 2014a). Baza za portugalski (Soares et al 2017) sadr`ava 3.800 rije~i i premda, ~ini se, sadr`ava podatke za razli~ite vrste rije~i, razlike me|u njima nisu navedene u istra`ivanju.…”
Section: Odnos Konkretnosti I Predo~ivostiunclassified
“…Primjerice, baza konkretnosti koju su izradili Brysbaert, Warriner i Kuperman (2014b) sadr`ava 40.000 engleskih leksema, me|utim bez podatka o vrsti rije~i kojoj pripadaju. Sli~na baza izra|ena je i za nizozemski (Brysbaert et al 2014a). Baza za portugalski (Soares et al 2017) sadr`ava 3.800 rije~i i premda, ~ini se, sadr`ava podatke za razli~ite vrste rije~i, razlike me|u njima nisu navedene u istra`ivanju.…”
Section: Odnos Konkretnosti I Predo~ivostiunclassified
“…Finally, to investigate the interplay of different psycholinguistic norms in the resource, we use a lexical database of age of acquisition and concreteness norms for Dutch (Brysbaert et al, 2014). Figure 6 shows the distribution of the norms per each attested level in the resource.…”
Section: Psycholinguistic Normsmentioning
confidence: 99%
“…Nevertheless, several studies have shown a positive relation between age of acquisition and word recognition response times when statistically controlling for word frequency, suggesting that age of acquisition has a unique effect (Brysbaert & Cortese, 2011;Juhasz, Yap, Dicke, Taylor, & Gullick, 2011;Kuperman, Stadthagen-Gonzalez, & Brysbaert, 2012). Estimates of age of acquisition were obtained from Brysbaert, Stevens, De Deyne, Voorspoels, and Storms (2014).…”
Section: Age Of Acquisitionmentioning
confidence: 99%
“…Hence, if the speeded word fragment completion task indeed involves more elaborate processing, as was suggested by Heyman et al (2015), one would expect a stronger relation between judged concreteness and response times. Concreteness ratings were again obtained from Brysbaert et al (2014). 4 Speeded word fragment completion variables Orthographic Levenshtein distance 20 distractor (OLD20D) In this context, the term Bdistractor^refers to the nonword formed by filling in the incorrect letter (e.g., tometo).…”
Section: Semantic Variablementioning
confidence: 99%
See 1 more Smart Citation